Trajectory control for autonomous electric vehicles with in‐wheel motors based on a dynamics model approach. Issue 5 (1st June 2016) - Li, Boyuan; Du, Haiping; Li, Weihua
Abstract : The trajectory control of autonomous vehicles is an area which has attracted much research recently because it can prevent accidents caused by driver errors and significantly improve road capacity. Overtaking is one of the most complex and challenging manoeuvres for road vehicles and the autonomous control of the vehicle during this manoeuvre can greatly improve vehicle safety. As the innovative four‐wheel independent steering (4WIS) and four‐wheel independent driving (4WID) electric vehicle can provide redundant control actuators, this study focuses on utilising 4WIS–4WID techniques and vehicle dynamics control to achieve better control of autonomous vehicles. This study first introduces the traditional two‐wheel proportional–integral–derivative (PID) steering control and two‐wheel sliding mode controller (SMC) driving control for autonomous vehicle control. Then based on these, the four‐wheel PID steering controller and four‐wheel SMC steering controller are proposed. A four‐wheel SMC driving controller and a four‐wheel combined yaw rate and longitudinal velocity SMC driving controller are also proposed. Simulation results prove that the best control performance can be achieved when the four‐wheel SMC steering controller and four‐wheel combined yaw rate and longitudinal velocity SMC driving controller are used together.